Health Benefits of Digital Videogames for Older Adults: A Systematic Review of the Literature - Hall, Amanda K.; Chavarria, E.; Maneeratana, Vasana; Chaney, B.; Bernhardt, J. (Games for health journal, 2012)
OBJECTIVE This article is a systematic review conducted of the research literature on digital videogames played by older adults and health outcomes associated with game play. Findings from each study meeting the inclusion criteria were analyzed and summarized into emergent themes to determine the impact of digital games in promoting healthy behaviors among older adults. MATERIALS AND METHODS A systematic review of the research literature was conducted through multiple academic databases for works, published between the years 2000 and 2011, looking at digital videogame interventions with adults 65 years of age and older. Multiple combinations of search terms and Boolean operators relevant to digital videogames and older adults were queried. A criteria matrix was created to code and evaluate studies. RESULTS Thirteen studies met specific criteria for inclusion and were analyzed in the final review. Significant mental, physical, and social health factors, type of digital game platform, study design, and measurements are among emergent themes summarized from the reviewed research literature. Significant mental health outcomes of digital game interventions were found in the majority of the reviewed studies, followed by physical and lastly social health outcomes in older adults. CONCLUSIONS A majority of the studies revealed significant positive effects on health outcomes associated with digital videogame play among older adults. With current advancements in technology, including advanced motion sensing, digital game platforms have significant potential for positive health impact among older populations. More robust and rigorous research designs are needed to increase validity and reliability of results and establish stronger causal relationships on the health benefits of digital videogame play for older adults.